Dialectics of Al-Dakhīl and Analytical Study of the Story Hārūt and Mārūt in Tafsir Mafātīḥ Al-Ġaib - Muhammad Agil Atoillah; Muhammad Luthfi Syarif; Abd. Kholid; Muhammad Irham Saryulis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
In the contemporary era, the infiltration of non-authentic narratives has permeated the discourse of Qur’anic interpretation. This phenomenon poses significant challenges. This article addresses the issue of how the story of Harūt and Mārūt has been infiltrated by data sources and has the potential to distort the divine meaning, as well as how al-dakhil plays a role in the epistemology of da’wah. The main objective of this study is to analyse the dialectical relationship of al-dakhīl in the interpretation of Mafātīḥ Al-Ġaib, focusing on the impact of this fictional infiltration narrative on Islamic da’wah discourse. To achieve this, a qualitative method encompassing a comprehensive review of literature and interpretations related to the story of Harūt and Mārūt serves as the foundation of the research methodology. The results of this study indicate that the spread of infiltrative narratives without preventive measures can lead to the degradation of fundamental Islamic values. These findings underscore the need for a responsible approach in explaining Islamic teachings. In another dimension, this article advocates for the validation of sources and the promotion of accurate interpretations. Ultimately, this research contributes to the ongoing discourse in the world of Qur’anic interpretation by emphasizing the importance of preserving authentic Islamic teachings in an increasingly contemporary world.